Building a rural workforce through identifying supports for rural, mature‐aged nursing and allied health students: A systematic scoping review. (25th September 2021) - Quilliam, Claire; Crawford, Nicole; McKinstry, Carol; Wong Shee, Anna; Harvey, Pamela; Glenister, Kristen; Sutton, Keith
Abstract: Introduction: There is a long‐standing undersupply of nursing and allied health professionals in rural Australia. Rural, mature‐aged people form an untapped section of rural communities that could help to address these workforce needs. There is little understanding of the supports required to assist rural, mature‐aged nursing and allied health students to complete their studies and enter the rural health workforce. Objective: To scope factors influencing rural, mature‐aged nursing and allied health students' ability to access, participate, and succeed in higher education. Design: A scoping review of the international rural nursing and allied health and education literature was undertaken. Five databases (CINAHL Complete, MEDLINE, Education Resources Information Center [ERIC], Embase, and Education Research Complete), key peer‐reviewed journals, and Australian grey literature were searched. Findings: Fourteen articles were included in the review. Ten studies described rural, mature‐aged nursing and allied health student characteristics, 6 described barriers to students participating and succeeding in higher education, and 4 described student supports. Discussion: This review found limited evidence to guide higher education providers in attracting, supporting and retaining rural, mature‐aged nursing and allied health students. In particular, evidence of student supports is required beyond those manifested by students themselves or their family, to include offerings from university and government sources. Conclusion: Substantially more research attention is needed to understand the experiences of rural, mature‐aged nursing and allied health students, and supports required for this cohort to access, participate and successfully complete higher education.